Necrotizing funisitis is an indicator that intra-amniotic inflammatory response is more severe and amnionitis is more frequent in the context of the extension of inflammation into Wharton's jelly - Ji Su Seong; Chan-Wook Park; Kyung Chul Moon; Joong Shin Park; Jong Kwan Jun (Elsevier, 2021)
Objective: Necrotizing funisitis (NF) is defined as the presence of an arc (i.e., crescent/band/ring/halos) of infiltrated neutrophils and/or associated debris in Wharton's jelly (WJ) of umbilical-cord (UC). However, no information exists about the comparison in intra-amniotic inflammatory-response (IAIR) and inflammation in extra-placental membranes between the presence and absence of NF in the context of inflammation in WJ among spontaneous preterm births (PTBs). The objective of current study is to examine this issue. Materials and methods: We examined IAIR and the frequency of amnionitis according to the progression of inflammation in UC (i.e. stage-1, umbilical phlebitis [inflammation in umbilical-vein(UV)] only; stage-2, involvement of at least one umbilical-artery[UA] and either the other UA or UV without extension into WJ; stage-3, the extension of inflammation into WJ without NF; stage-4, the extension of inflammation into WJ with NF) in 120singleton spontaneous PTBs (<37weeks). IAIR was gauged by AF MMP-8 (ng/ml) within 3days before birth. Results: 1) Stage-1, stage-2, stage-3, and stage-4 were present in 20%(24/120), 6%(7/120), 61%(73/120), and 13%(16/120) of cases respectively; 2) AF MMP-8 continuously increased (stage-1 vs. stage-2 vs. stage-3 vs. stage-4; median[ng/ml], range[ng/ml]; 207.2[16.8-1196.5] vs. 444.1[8.5-2608.0] vs. 458.8[0.4-3116.7] vs. 1859.7[912.3-5304.8]; Spearman's rank correlation-test, α = 0.454, P = 0.006), and the frequency of increased AF MMP-8 (≥854.1 ng/ml) elevated (stage-1 vs. stage-2 vs. stage-3 vs. stage-4; 13%[1/8] vs. 33%[1/3] vs. 32%[6/19] vs. 100%[5/5]; Linear-by-linear-association, P = 0.012) with the progression of inflammation in UC; 3) Moreover, there was a stepwise increase in the frequency of amnionitis according to the progression of inflammation in UC (stage-1, 33%[8/24]; stage-2, 43%[3/7]; stage-3, 62%[45/73]; stage-4, 81%[13/16]; Linear-by-linear-association, P = 0.001). Conclusion: NF is an indicator that IAIR is more severe and amnionitis is more frequent in the context of the extension of inflammation into WJ. Therefore, current study confirms that NF is the most advanced stage in the progression of inflammation within UC.